Harmonically trapped fermions in one dimension: a finite-temperature lattice Monte Carlo study - Attanasio, Felipe; Bauer, Marc; Kapust, Renzo; Pawlowski, Jan M. (Physical review, 2024)
We study a one-dimensional two-component Fermi gas in a harmonic trapping potential using finite-temperature lattice quantum Monte Carlo methods. We are able to compute observables in the canonical ensemble via an efficient projective approach. Results for density profiles, correlations, as well as energy-related observables are presented for systems with up to 80 particles and various temperatures. Our simulations reproduce known numerical results and compare well against available experimental data close to the ground state, while at higher temperature they are benchmarked against the exact solution of the two-particle system. This provides an indication that a standard lattice discretization is sufficient to capture the physics of the trapped system. In the special case of a spin-imbalanced gas, we find no sign problem in the studied parameter ranges, allowing access without the need of specialized methods. This includes simulations close to the ground state and at large population imbalance, where we present results for density correlations, indicating pairing at finite total momentum.